UJI KESTABILAN KALIUM FERAT - Nur Hayati, ; Nita Kusumawati, ; Bertha Yonata, (Matematika dan Sains, 2009)
The synthesis of potassium ferrate and the optimazion as green chemistry degradator had been studied. The purpose of research was to study the influence of pH and reaction time to potassium ferrate stability. This research was started by synthesis and characterization of potassium ferrate. Some parameters influencing degradation process by ferrate ion, such as pH and molar reaction time have been studied, and the decomposition result was quantization by spectrophotometry UV-Vis. Based on the XRD spectra, it was found that the solid phase potassium ferrate had a tetrahedral structure with a space group of D2h(Pnma). The potassium ferrate solution had a maximum stability at pH 9-10. Decomposition result of ferrate indicated that kinetic constant was stable at spanning time 24-72 hours.2h(Pnma). The potassium ferrate solution had a maximum stability at pH 9-10. Decomposition result of ferrate indicated that kinetic constant was stable at spanning time 24-72 hours.